Antimicrobial Activity of Coronarin D and Its Synergistic Potential with Antibiotics. (14th May 2014) - Reuk-ngam, Nanthawan; Chimnoi, Nitirat; Khunnawutmanotham, Nisachon; Techasakul, Supanna
Abstract : Coronarin D is a labdane-type diterpene from the rhizomes of Hedychium coronarium . In the view of our ongoing effort to explore its novel biological activity, antimicrobial activity study of coronarin D was performed. The results showed that coronarin D was active against tested Gram-positive bacteria, inactive for tested Gram-negative bacteria, and weakly active against tested fungi. The antibacterial effect of the combination of coronarin D with nine classical antibiotics against four Gram-positive bacteria was also evaluated. The fractional inhibitory concentration indices (FICI ) of coronarin D-antibiotics combinations, calculated from the checkerboard assay, were used as synergism indicator. Out of 36 combinations, 47% showed total synergism, 33% had partial synergistic interaction, 17% showed no effect, and 3% showed antagonism. By combination with coronarin D at concentration of 0.25 minimal inhibitory concentration (MIC), the activities of antibiotics were boosted to 4- to 128-fold. These finding suggested an attractive approach to combat the infectious diseases by using coronarin D-antibiotic drug combination.